Treatment of 52 patients with a self-adhesive siliconised superabsorbent dressing: a multicentre observational study. (2nd June 2020) - Barrett, Simon; Rippon, Mark; Rogers, Alan A.
Abstract : Objective: To provide 'in use' clinical data to support exudate management in patients with moderately to highly exuding wounds with bordered superabsorbent wound dressing with a silicone adhesive interface. Method: This study was an open-labelled non-comparative study. Patients included in the study were selected by the clinical investigator(s) according to whether the patient required a dressing for the management of moderately to highly exuding wounds. Results: The primary aim of this study was to evaluate the clinical objective in relation to exudate handling (moderate to high) with a superabsorbent silicone border dressing (Zetuvit Plus Silicone Border; SAP silicone border dressing; designated RespoSorb Silicone Border in some countries). The SAP border dressing had met the clinical objectives relating to exudate management, affirmed by the health professionals with a yes response in 94% of cases. Additionally, the health professionals rated the handling of exudate as excellent/good (78%) and most (80%) reported that they would use the SAP silicone border dressing again. Allied to this was the fact that the SAP silicone border dressing improved the wound edge and periwound skin conditions (29% and 36% of patients, respectively). Regarding dressing retention, the SAP silicone border dressing retained its position in 72% of patients. For wear time, the largest proportion of dressing changes, both pre-study and during the evaluation period, was every third day (45% and 44%, respectively). But there was a shift to extended wear time with use of the SAP silicone border dressing with 72% of patients' dressing changes being every third day or longer. Conclusion: The SAP silicone border dressing was successful in managing wound exudate in moderately to highly exuding wounds and consequently this had a beneficial impact on the wound edge and periwound skin. Overall, there was a positive effect on wound bed preparation and in turn the healing response was progressive. This study has shown that the SAP silicone border dressing successfully controlled exudate and provided positive benefits when used in the treatment of patients with moderately to highly exuding wounds.